STRATEGI KOMUNIKASI KPID JAWA TIMUR DALAM PENCEGAHAN PENYEBARAN VIRUS CORONA - Putri, Amalia Rosyadi; Retpitasari, Ellyda (KOMUNIKE: Jurnal Komunikasi Penyiaran Islam, 2020)
This research is motivated by a phenomenon that occurred in early March 2020, the Indonesian people were shocked by the Corona pandemic outbreak, this outbreak originating from China, finally infecting Indonesian society. Broadcast media, both television and radio, are competing to broadcast the Corona outbreak. Indonesian Broadcasting Commission (KPID) East Java as an independent state institution participates in overcoming panic and efforts to prevent the Corona outbreak. The purpose of this study is to describe and find out the communication strategy of the KPID East Java in preventing the spread of the Corona outbreak. The theory used is the analysis of The Pervasive Presence. The method used is qualitative using a phenomenological approach. The results of this study found that the communication strategy of the KPID East Java in dealing with the spread of the Corona outbreak consisted of three strategies, namely by live talk shows on television and radio, distributing circulars to radio and television broadcasting institutions throughout East Java via email and WhatsApp, and publication of information through social media and public sphere, namely the KPID East Java Instagram. These three communication strategies are part of the task of the KPID East Java in supervising broadcasting institutions and media literacy to the public.